Pengaruh Islamic human development index dan pertumbuhan ekonomi terhadap ketimpangan pendapatan di Indonesia tahun 2019-2023 - Lestari, Jelita Ayu; Iqbal, Muhammad; Saefurrohman, Ghina Ulfah (AL-Muqayyad, 2025)
This study aims to analyze the effect of the Islamic Human Development Index (I-HDI) and economic growth on income inequality in Indonesia during the 2019-2023 period. The research employs a quantitative approach using secondary data from 34 provinces in Indonesia, obtained from the Central Statistics Agency (BPS) and other official sources. The analysis method applied is panel data regression, with the best model selected through the Chow and Hausman tests, which confirmed the Fixed Effect Model (FEM) as the most appropriate estimation model. The results show that partially, I-HDI has no effect on income inequality, while economic growth has a negative and significant effect. Simultaneously, I-HDI and economic growth have a significant effect on income inequality, with a contribution of 57.1%, while the remaining 42.9% is explained by other factors outside the model. These findings emphasize that inclusive economic growth plays an important role in reducing inequality, while improving human development quality based on maqaşid al-shari'ah requires more equitable distribution to optimally reduce income disparity.